2021
DOI: 10.3390/polym13060914
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Polyanions and Polycations on Bacteriophage Activity

Abstract: Phage therapy is a great alternative to antibiotic drugs, but it can’t effectively overcome the over-acidic medium of the stomach. We offer the use of polyelectrolyte microcapsules as a protective means of bacteriophage. It is necessary to understand the influence of polyelectrolytes on bacteriophage survival. The work studied the effect of polyanions and polycations on the coliprotetic bacteriophage’s viability. We have shown that polyallylamine decreased bacteriophage’s viability during increasing polyelectr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…As a result, after the addition of capsules to the nutrient medium with the subsequent destruction of the PMC shell, it was shown that there was no bacteriophage activity. This effect may be related to the destruction of the shell by a proteinase with the subsequent release of monomers and dimers of the polyarginine shell, which may be the cause of bacteriophage inactivation [ 56 , 57 ].…”
Section: Resultsmentioning
confidence: 99%
“…As a result, after the addition of capsules to the nutrient medium with the subsequent destruction of the PMC shell, it was shown that there was no bacteriophage activity. This effect may be related to the destruction of the shell by a proteinase with the subsequent release of monomers and dimers of the polyarginine shell, which may be the cause of bacteriophage inactivation [ 56 , 57 ].…”
Section: Resultsmentioning
confidence: 99%
“…Unfortunately, polycations exhibit significant cytotoxicity, and thus they can be harmful to living organisms. 8,9 Therefore, more and more attention is paid to understanding the potential environmental impacts of polycationic nanomaterials.…”
Section: Introductionmentioning
confidence: 99%
“…To the best of our knowledge, the only report of antiphage polymer is dextran, dextran sulfate, and polystyrene sulfate, which show some limited inhibition but have been neither widely explored nor compared to other polymers, and their mode of action is not studied. 37 Here we report the novel discovery that poly(acrylic acid) (PAA) is a potent inhibitor of bacteriophage infection. A library of polymers was screened, showing this material to be uniquely active, even compared to other poly(carboxylic acid)s. The polymer prevents infection and is shown to not interfere with recombinant protein expression procedures in bacteria.…”
mentioning
confidence: 99%
“…It has recently been demonstrated that sulfated polymers, which mimic heparin sulfate anchors on cell membranes, are broad-spectrum virucides against a range of human pathogenic viruses. , Poly­(carboxylic acid)­s have been reported to inhibit human viruses. , It is also well-established that polymers can be deployed as antibacterial agents, mimicking cationic host-defense peptides. A polymeric/biomaterials approach to address phage contamination may offer a scalable and practical solution. To the best of our knowledge, the only report of antiphage polymer is dextran, dextran sulfate, and polystyrene sulfate, which show some limited inhibition but have been neither widely explored nor compared to other polymers, and their mode of action is not studied …”
mentioning
confidence: 99%
See 1 more Smart Citation